Guidelines for investigating chemical process incidents. (American Institute of Chemical Engineers, 2003)
This book provides a valuable reference tool for technical and management personnel who lead or are a part of incident investigation teams. This second edition focuses on investigating process-related incidents with real or potential catastrophic consequences. It presents on-the-job information, techniques, and examples that support successful investigations. The methodologies, tools, and techniques described in this book can also be applied when investigating other types of events such as reliability, quality, occupational health, and safety incidents. The accompanying CD-ROM contains the tex.